Alpha-Ketoglutarate Supply for Amino Acid Synthesis in Higher Plant Chloroplasts: Intrachloroplastic Localization of NADP-specific Isocitrate Dehydrogenase - Elias, Bin A. (1977)
Isocitrate dehydrogenase was found in Pisum sativum chloroplasts purified on sucrose density gradients. A chloroplast-enriched pellet obtained by differential centrifugation formed two chlorophyll-containing bands. The lower one containing intact chloroplasts had NADP-specific isocitrate dehydrogenase and triose-phosphate isomerase activities. Mitochondria and peroxisomes were observed to band well away from the intact chloroplast region, as indicated by peak activities of fumarase and catalase, respectively. The presence of isocitrate dehydrogenase in chloroplasts suggests that chloroplasts may generate at least some of the α-ketoglutarate required for glutamate synthesis.